Biomechanical aspects of soccer performances - Luhtanen, P. (coachesinfo.com)
This presentation aboutthe biomechanical techniques will focus mainly on the suggestions relating to the better understanding and improved performance of the players and teams with safety methods. Contents: - Individual skills in soccer - Control of skillful movement - Individual skills - Basic movements in soccer - Higher level skills in soccer